The biogeographical speciations of shiitake Lentinula edodes and a new species Lentinula platinedodes sp. nov. found in Cat Tien, South Vietnam - Tham, Le Xuan; Chuong, Nguyen Nhu; Duong, Pham Ngoc; Thiem, Bui Hoang (Academia Journal of Biology, 2012)
Lentinula edodes (Berk.) Pegler has been taxonomically studied for 130 years ago with collections of authentic specimens as type of Lentinus tonkinensis Pat. (already treated as synonym), collected from Ba Vi mountainous region (near to Hanoi) by Balansa (1887-1888), deposited in Paris (Patouillard, 1928) and recently supplemented with some newly - collected strains, native to high mountainous regions, North Vietnam: Cao Bang and Sa Pa shiitake, near to South China. Some Shiitake strains obtained from Japan, China as repesentatives of East Asian races of Lentinula edodes were analysed comparatively both morphological and molecular characteristics, showing that the Vietnam natively geographical races of Shiitake collected in Sa Pa mountains (1600-2800 m alt.), North Vietnam are so clearly segregated from strains imported from Changsha, Yunnan (China) and Tottori (Japan) - that are East Asian races, typical temperate Shiitake Lentinula edodes (similar to Cao bang race), that markedly similar to Southeast Asian - tropical Shiitake forms, but close to the species Lentinula lateritia and L. novaezelandieae, based on rDNA both D and ITS sequences. In South Vietnam, Shiitake races of Lentinula edodes, L. cf. lateritia and L. platinedodes sp.nov. were newly found on Langbiang mountain (1500-2000 m alt.) in Da Lat city, highland of Lam Dong province and in Cat Tien national park (600-150 m alt.), lowerland of Dong Nai province, particularly among which the last one is showing high similarity in morphological characters with both Amarica’s Shiitake - type species, Lentinula boryana and L. edodes, due to the forms at different stages of development of fruitbodies, collected in the wild. This new species showed some phenotypte forms similar to each others in their early stages of morphological genesis of young fruitbodies in nature and in cultivations. However, they are the same in rDNA sequences, particularly located in the clades of New World Shiitake lineage. They share common secondary tropically features of speciations in the Lentinula, and their ontogenesis of fruitbodies shows the more primary fibrilose forms of Lentinula edodes differentiating to the secondary glabrous froms commonly found in species in South East Asia - Australian regions. The occurrence of tropical Shiitake both L. cf. lateritia and L. platinedodes in Vietnam would be a new evidence for direct relationships present between Old and New World Shiitake speciation lineages, that China - South East Asia regions would be an origin center of diversity of Lentinula, and the South East Asia - Australian regions would be a focus of tropical and subtropical diversity of Shiitake speciations and harbor Lentinula morphological species with high similarity and compatibility, and the temperate Shiitake races from the pivotal species Lentinula edodes differenciate and disperse, so largely in Australasia, particularly under cultivation, selection and breeding.